Effects of binary solvent extraction system, extraction time and extraction temperature on phenolic antioxidants and antioxidant capacity from mengkudu (Morinda citrifolia). - Thoo, Yin Yin; Ho, Swee Kheng; Liang, Jia Yun; Ho, Chun Wai; Tan, Chin Ping (Elsevier, 2010)
An investigation into the effects of ethanol concentration (0–100%, v/v), extraction time (20–120 min) and extraction temperature (25–65 °C) on the extraction of phenolic antioxidants from mengkudu (Morinda citrifolia) was performed using a single-factor experiment. Total phenolic content (TPC) and total flavonoid content (TFC) assays were used for determination of phenolic compounds. Antioxidant capacity was evaluated by measuring the scavenging effect on 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and 2,2′-diphenyl-1-picrylhydrazyl (DPPH) radicals. Experimental results showed that extraction conditions had significant effect on extraction of phenolic compounds and antioxidant capacities. The optimised conditions were 40% ethanol for 80 min at 65 °C, with values of 919.95 mg GAE/100 g DW for TPC, 472.73 mg CE/100 g DW for TFC, 791.71 μmol TEAC/100 g DW for ABTS and 1928.5 μmol TEAC/100 g DW for DPPH. TPC was significantly correlated with DPPH under the effects of ethanol concentration (r = 0.932) and extraction time (r = −0.938).